Epithelial barrier dysfunction and microbial dysbiosis: exploring the pathogenesis and therapeutic strategies for Crohn’s disease - AKKOÇ, TUNÇ (My University, 2024)
Crohn’s disease (CD), a chronic gastrointestinal inflammatory disease, is becoming more widespread worldwide. Crohn’s disease is caused by gut microbiota changes, genetics, environmental stresses, and immunological responses. Current treatments attempt to achieve long-term remission and avoid complications, delaying disease progression. Immunosuppressive measures and combination medicines should be started early for high-risk patients. These medicines monitor inflammatory indicators and adjust as needed. The epithelial barrier helps defend against physical, chemical, and immunological threats. When tissues’ protective barrier breaks down, the microbiome may reach the layer underneath. Unbalanced microbial populations and inflammation impair healing and adjustment. Inflammatory cells infiltrating sensitive tissues aggravate the damage and inflammation. This approach promotes chronic inflammatory diseases. The epithelial barrier hypothesis states that hereditary and environmental variables cause epithelial tissue inflammation. This review focuses on how epithelial barrier break-down and microbial dysbiosis cause Crohn’s disease and current advances in understanding the epithelial barrier, immune system, and microbiome. Additionally, investigate treatments that restore barrier integrity and promote microbial balance. Overall, it stresses the role of epithelial barrier failure and microbial dysbiosis in Crohn’s disease development and discusses current advances in understanding the barrier, immunological responses, and microbiota.
Keywords: Tıp; Histoloji-Embriyoloji; Cerrahi Tıp Bilimleri; Patoloji; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyokimya; Temel Bilimler; Medicine; Histology and Embryology; Surgery Medicine Sciences; Pathology; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Health Sciences; Fundamental Medical Sciences; Biochemistry; Natural Sciences; Yaşam Bilimleri (Life); Biyoloji Ve Biyokimya; Moleküler Biyoloji Ve Genetik; Hücre Biyolojisi; Biyokimya Ve Moleküler Biyoloji; Life Sciences (Life); Biology & Biochemistry; Molecular Biology & Genetics; Cell Biology; Biochemistry & Molecular Biology; Histoloji; Histology; Crohn’s disease pathogenesis; epithelial barrier dysfunction; immune responses; microbial dysbiosis; therapeutic strategies